Pengaruh Komitmen Organisasi, Locus Of Control Dan Implementasi Good Governance Terhadap Kecenderungan Kecurangan (Fraud) Akuntansi Pada Lembaga Perkreditan Desa Di Kecamatan Seririt - komang rosa lyana; Edy Sujana (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the effect of organizational commitment, locus of control and implementation of good governance on the tendency of accounting fraud in village credit institutions in Seririt District. The population used by researchers in this study were all LPD in Seririt District, totaling 25 LPD. The sampling technique used is purposive sampling. The number of samples in this study were 21 LPD with a total of 63 respondents. The data analysis technique in this study is quantitative using multiple linear regression analysis with the help of SPSS version 24.0 for windows. The results of the study show that (1) organizational commitment has a negative and significant effect on the tendency of accounting fraud at LPD in Seririt District, (2) locus of control has a positive and significant effect on the tendency of accounting fraud in LPDs in Seririt District, (3) the implementation of good governance has a negative and significant effect on the tendency of accounting fraud at the LPD in Seririt District.